The anxiety behind the screen: exploring the relationship between knowledge-based videos engagement and learning anxiety among postgraduate entrance exam candidates, mediated by self-efficacy - Xu, Kunjin; Bao, Liangye; Zhang, Dan (Frontiers in Psychology, 2025)
BackgroundKnowledge-based videos play a crucial role in preparing for postgraduate entrance exams (PEE). However, they may also contribute to learning anxiety.ObjectiveThis study examines the relationship between knowledge-based videos engagement and learning anxiety among PEE candidates, focusing on the mediating role of self-efficacy. The findings will offer empirical guidance for using knowledge-based videos to alleviate learning anxiety.MethodsFrom September 4 to 30, 2024, a convenience sampling method was used to survey 466 candidates preparing for the 2025 national PEE in China. Data were collected through the Knowledge-based Videos Engagement Questionnaire, the Learning Anxiety Questionnaire, and the Self-efficacy Questionnaire. A mediation analysis was conducted using Hayes’ PROCESS macro with Bootstrap resampling (5,000 replications), and significance was assessed with 95% confidence intervals.ResultsThe mean learning anxiety of the knowledge video engagement group was significantly higher than that of the non-engagement group, whereas the mean self-efficacy of the engagement group was significantly lower. ANOVA revealed significant differences in learning anxiety across varying levels of knowledge-based videos engagement. Notably, no significant difference was observed between the “none” and “mild” engagement categories. However, “moderate” engagement emerged as a critical threshold, with “moderate,” “severe,” and “extremely severe” engagement correlating with significantly increased learning anxiety. Mediation analysis indicated that knowledge-based videos engagement did not directly predict learning anxiety. Nevertheless, it was found to significantly and positively predict learning anxiety through the mechanism of self-efficacy.ConclusionBoth moderate and higher levels of knowledge-based videos engagement are associated with a significant increase in learning anxiety among PEE candidates, with self-efficacy acting as a complete mediator in this relationship. It is recommended that PEE candidates should adopt balanced video usage strategies and enhance their self-efficacy to reduce anxiety and improve learning outcomes.